A gift from Oxford: the Osler-Thomas connection - Golden, Richard L. (Baylor Health Care System, 2012)
In June 1926, Dr. Henry M. Thomas Jr. (“Hal”) received as a gift from Grace Osler in Oxford an Einhorn Duodenal Bucket Set that had belonged to Sir William Osler. The Thomases were a distinguished multigenerational physician family of Baltimore with high educational standards and major accomplishments in medicine and medical education. An extraordinary number of the Thomas women earned doctorates and made significant contributions in an era when this was a pioneering achievement. This is exemplified by Martha Carey Thomas, who earned a PhD in 1882 and served as dean and president of Bryn Mawr College for women. As a leading feminist and member of the Women's Fund Committee, she was a major force in providing the endowment that permitted the opening of the Johns Hopkins School of Medicine under the strict stipulations that admission requirements include an undergraduate degree and that women be admitted on the basis of total equality with men. Osler established relationships that extended over three generations of the Thomas family during his Baltimore tenure, an influence that proved mutually beneficial.